Sexual Violence in the Islamic Law Perspective: Aceh Islamic Law and Local Wisdom Approach - Danial Danial; Yoesrizal M. Yoesoef; Nur Sari Dewi. M (Ulumuna, 2023)
The study aims to examine the integration of religious values, Aceh culture, and global issues, which form the Sexual Violence Crime Law (UU-TPKS). This article is a qualitative study with a descriptive approach where the primary data were obtained through interview and group discussion. The study used relevant sources from books, journals, and articles related to the chosen theme as the secondary data. This study shows that integration of religious values into the Sexual Violence Crime Law (UU-TPKS) is necessary because Indonesian law must be based on the Pancasila philosophy as a result of the translation into Islamic values. It further shows that religious, cultural, and global values embodied in that law are the values of tauhid, justice, freedom, kindness, cooperation, equality, and tolerance. The state must measurably implement all values and derive them into laws and regulations. The study also reveals that such an integration reflects the integration of religious principle and values and local wisdom described in various meanings and symbols. Keywords: Islamic Law, Sexual Violence, Local Wisdom, Aceh